P–805 Artificial oocytes: from somatic cells to fertile pups. (6th August 2021) - Kocur, O; Trout, A; Xie, P; Petrini, A; Rosenwaks, Z; Palermo, G
Abstract: Study question: We analyzed the efficacy of generating artificial oocytes using somatic cells (SCs) from two mouse strains (B6D2F1 and FVB) and followed their full pre-/post-implantation development. Summary answer: While artificial oocytes generated from the new strain (FVB) had higher fertilization rates, those from the standard strain (B6D2F1) provided expanded blastocysts and fertile pups. What is known already: B6D2F1 is a popular hybrid mouse strain for cloning and transgenic creation due to its geno-/pheno-typic uniformity and high oocyte yield and quality. Indeed, B6D2F1 oocytes have a distinct metaphase II (MII) spindle complex, making them an ideal candidate to generate ooplasts used in SC nuclear transfer (SCNT). However, because they lack genetic variance, they are less suitable for reciprocal SCNT studies. In contrast, FVB mice have single nucleotide polymorphisms and indels on each chromosome that can aid in tracing the pedigree of progeny. Study design, size, duration: A total of 10 experiments were performed over the course of 3 months, using 30 stimulated mice. SCs were retrieved from cumulus oophorus harvested from FVB and B6D2F1 mice. SCs from both strains were injected into enucleated MII B6D2F1 oocytes. Unmanipulated B6D2F1 oocytes were piezo-ICSI inseminated, serving as controls. The occurrence of haploidization, fertilization, and full preimplantation development was compared. Some blastocysts were transferred into pseudo-pregnant CD–1 mice to obtain offspring. Participants/materials, setting, methods: Oocyte enucleation was performed under Oosight™ visualization and cytochalasin B exposure. An FVB or B6D2F1 SC was transferred into the perivitelline space of the ooplast with Sendai virus to promote fusion. Haploidization was monitored by pseudo-meiotic spindle formation followed by extrusion of a pseudo-polar body after insemination. Conceptuses were cultured in a time-lapse imaging system, with piezo-ICSI controls. Expanded blastocysts were transferred into uterine horns of pseudo-pregnant mice. Offspring were mated to test their fertility. Main results and the role of chance: FVB (n = 278) and B6D2F1 (n = 905) SCs at G0 phase, with a diameter <10 mm, were chosen for SCNT and transferred into enucleated B6D2F1 ooplasts. Enucleation of 1, 212 oocytes yielded a survival rate of 97.6%. Both FVB and B6D2F1 SCNT resulted in similar survival rates of 100% and 98.5%, respectively. Successful haploidization, determined by the presence of a pseudo-meiotic spindle 2 hours after SCNT, was also comparable, with 59.9% of FVB and 63.7% of B6D2F1. Survival after piezo-ICSI was also comparable between FVB- and B6D2F1-reconstituted oocytes, with rates of 64.3% and 60.3%, respectively, albeit lower than the control (75.2%, P < 0.00001). FVB embryos fertilized at a rate of 88.7%, comparable to the control zygotes at 85.8%, while B6D2F1 conceptuses demonstrated a lower fertilization rate (70.8%, P < 0.00001). Blastulation of FVB- and B6D2F1-derived embryos was 15.1% and 24.0%, respectively, while the control was 80.7% (P < 0.00001). Whole-genome karyotyping of 9 B6D2F1-derived blastocysts confirmed 5 of the samples to be euploid. FVB blastocysts (N = 8) and B6D2F1 blastocysts (N = 81) were transferred into pseudo-pregnant mice, resulting in 3 fertile offspring only from the B6D2F1 conceptuses. Limitations, reasons for caution: This is still a limited number of observations, and pups were delivered only from the B6D2F1 strain. The utilization of a strain with higher genetic variance may help facilitate offspring fingerprinting. Wider implications of the findings: This study demonstrates the ability to generate artificial genotyped conceptuses, yielding live offspring. The identification of a feasible donor cell, together with optimization of cell cycle stage and standardization of post-implantation development, will help promote this technique for human reproduction in couples with age-related infertility or poor ovarian reserve. Trial registration number: N/A